Latvia : Report on the Observance of Standards and Codes on Accounting and Auditing - World Bank Group (World Bank, Washington, DC, 2016)
This assessment of accounting and auditing practices in Latvia is part of a joint initiative of the World Bank and International Monetary Fund (IMF) to prepare Reports on the Observance of Standards and Codes (ROSC). One of the twelve ROSC modules focuses on Accounting and Auditing (A&A), this assessment addresses the strengths and weaknesses of the accounting and auditing environment that influence the quality of corporate financial reporting and includes a review of both mandatory requirements and actual practice. This is the second A&A ROSC for Latvia. The first one was published in 2005.